A precise and sustainable doxycycline-inducible cell line development platform for reliable mammalian cell engineering with gain-of-function mutations - Shin, Sung Wook; Min, Honggi; Kim, Jiwon; Lee, Jae Seong (Metabolic Engineering, 2024)
For mammalian synthetic biology research, multiple orthogonal and tunable gene expression systems have been developed, among which the tetracycline (Tet)-inducible system is a key tool for gain-of-function mutations. Precise and long-lasting regulation of genetic circuits is necessary for the effective use of these systems in genetically engineered stable cell lines. However, current cell line development strategies, which depend on either random or site-specific integration along with antibiotic selection, are unpredictable and unsustainable, limiting their widespread use. To overcome these issues, we aimed to establish a Robust Overexpression via Site-specific integration of Effector (ROSE) system, a clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9-mediated streamlined Tet-On3G-inducible master cell line (MCL) development platform. ROSE MCLs equipped with a landing pad facilitated the transcriptional regulation of various effector genes via recombinase-mediated cassette exchange. Long-term investigation revealed that the modular design of genetic payloads and integration sites significantly affected the induction capacity and stability, with ROSE MCLs exhibiting exceptional induction performance. To demonstrate the versatility of our platform, we explored its efficiency for the precise regulation of selection stringency, manufacturing of therapeutic antibodies with tunable expression levels and timing, and transcription factor engineering. Overall, this study demonstrated the effectiveness and reliability of the ROSE platform, highlighting its potential for various biological and biotechnological applications.
Keywords: Cell line development; Cell lines; Epigenetic silencing; Gain-of function; Gain-of-function mutation; Inducible systems; Mammalian synthetic biology; Site-specific; Site-specific integration; Synthetic biology; Tetracycline-on3g inducible system; Animals; Cell Engineering; Cell Line; CRISPR-Cas Systems; Doxycycline; Gain of Function Mutation; HEK293 Cells; Humans; Cell line development; Epigenetic silencing; Gain-of-function mutations; Mammalian synthetic biology; Site-specific integration; Tet-On3G inducible system